Palladium(ii)-catalyzed ortho-C–H olefination of phenylalanine and phenylethylamine derivatives directed by removable picolinamide group. Issue 40 (10th May 2017) - Zhao, Fei; Jia, Xiuwen; Zhao, Jingwei; Fei, Chaoli; Liu, Liyang; Liu, Guannan; Wang, Dongping; Chen, Fei
Abstract : Palladium-catalyzed ortho -C–H olefination of phenylalanine and phenylethylamine derivatives assisted by a removable picolinamide group has been achieved. Abstract : Palladium-catalyzed ortho -C–H olefination of phenylalanine and phenylethylamine derivatives assisted by a removable picolinamide group has been achieved. This protocol shows broad substrate scope, functional tolerance and moderate to high yields, thus affording a practical approach for the direct modification of phenylalanine and phenylethylamine derivatives.